Use of stability statistics in the selection of Clausena heptaphylla (Roxb.) Wight & Arn for novel anethole rich strain (Jor Lab CH-2) - Lal, Mohan; Munda, Sunita; Gogoi, Anindita; Begum, Twahira; Baruah, Joyashree; Chanda, Sanjoy K.; Lekhak, Himangshu (Frontiers in Plant Science, 2022)
Anethole is an industrially important compound which is extensively used in pharmaceuticals, cosmetics, perfumery, food and confectioneries. Anethole is primarily obtained from fennel, anise, and star anise which is highly expensive. Therefore, a study was performed to identify a cost-effective and natural anethole rich strain of Clausena heptaphylla through selection and confirmed through multilocation trial. The study was conducted using 23 accessions collected from North eastern region of India from 2014-2018 (initial evaluation trial) and 2018-2022 (multilocation trial). Five agronomical traits along with essential oil yield and anethole content were evaluated which led to the identification of anethole rich variety of C. heptaphylla. This identified strain was further evaluated along with the two check varieties for stability based on three yield parameters viz. herbage yield, essential oil yield and anethole content at four multi-locations for four years. The identified superior line showed consistent performance across all the environments maintaining its superiority. The variety was named as Jor Lab CH-2 which exhibited average herbage yield of 1.2 Kg/plant/cutting and essential oil yield of 1.22%. The GC-MS analysis of the essential oil depicted trans anethole as the major constituent (93.25%) followed by estragole (4.85%) while benzene, 1,2-dimethoxy-4-(1-propenyl Isoeugenolmethyl ether and cis-anethole were the trace components. This is the first novel report of anethole rich variant of C. heptaphylla which has undergone multilocational trial over the years. Jor Lab CH-2 variety will open a new scope for the industries to isolate anethole from a different source in a cost-effective approach.